Central and peripheral adiposity and premenopausal breast cancer risk: a pooled analysis of 440,179 women - Minouk J. Schoemaker; Taylor Ellington; Hazel B. Nichols; Lauren B. Wright; Michael E. Jones; Katie M. O’Brien; Clarice R. Weinberg; Hans-Olov Adami; Laura Baglietto; Kimberly A. Bertrand; Yu Chen; Jessica Clague DeHart; et al. (Breast Cancer Research)
Abstract Background Among premenopausal women, higher body mass index (BMI) is associated with lower breast cancer risk, although the underlying mechanisms are unclear. Investigating adiposity distribution may help clarify impacts on breast cancer risk. This study was initiated to investigate associations of central and peripheral adiposity with premenopausal breast cancer risk overall and by other risk factors and breast cancer characteristics. Methods We used individual-level data from 14 prospective cohort studies to estimate hazard ratios (HRs) for premenopausal breast cancer using Cox proportional hazards regression. Analyses included 440,179 women followed for a median of 7.5 years (interquartile range: 4.0–11.3) between 1976 and 2017, with 6,779 incident premenopausal breast cancers. Results All central adiposity measures were inversely associated with breast cancer risk overall when not controlling for BMI (e.g. for waist circumference, HR per 10 cm increase: 0.92, 95% confidence interval (CI): 0.90–0.94) whereas in models adjusting for BMI, these measures were no longer associated with risk (e.g. for waist circumference: HR 0.99, 95% CI: 0.95–1.03). This finding was consistent across age categories, with some evidence that BMI-adjusted associations differed by breast cancer subtype. Inverse associations for in situ breast cancer were observed with waist-to-height and waist-to-hip ratios and a positive association was observed for oestrogen-receptor-positive breast cancer with hip circumference (HR per 10 cm increase: 1.08, 95% CI: 1.10–1.14). For luminal B, HER2-positive breast cancer, we observed an inverse association with hip circumference (HR per 10 cm: 0.84, 95% CI: 0.71–0.98), but positive associations with waist circumference (HR per 10 cm: 1.18, 95% CI: 1.03–1.36), waist-to-hip ratio (HR per 0.1 units: 1.29, 95% CI: 1.15–1.45) and waist-to height ratio (HR per 0.1 units: 1.46, 95% CI: 1.17–1.84). Conclusions Our analyses did not support an association between central adiposity and overall premenopausal breast cancer risk after adjustment for BMI. However, our findings suggest associations might differ by breast cancer hormone receptor and intrinsic subtypes.